Metabolomic and transcriptomic analyses unveil the accumulation of shikimic acid in the leaves of Ginkgo biloba - Yu, Wanwen; Cai, Minyue; You, Chenxi; Wei, Wenxuan; Liu, Huimin (Frontiers in Plant Science, 2025)
IntroductionShikimic acid, as a critical precursor for oseltamivir synthesis in antiviral pharmaceuticals, faces escalating global demand. Although Ginkgo biloba leaves have emerged as a promising natural source of shikimic acid owing to their exceptional content of this valuable compound and substantial biomass production capacity, the molecular mechanisms underlying its biosynthesis and downstream metabolic regulation in G. biloba leaves remain largely unknown.MethodsHere, the concentration of shikimic acid in 33 clones were assessed, and 1# (referred as HS) had the highest level. The shikimic acid content in HS was 119% higher than that in 24# (referred as LS), which possessed the lowest shikimic acid level. Concurrently, we analyzed downstream metabolites including flavonoids, phenylalanine, tryptophan and tyrosine, along with transcriptomic and metabolomic profiles in HS and LS.ResultsThe concentrations of flavonoids, phenylalanine, tryptophan and tyrosine in HS were markedly lower than those in LS. Principal component analysis (PCA) and partial least squares discriminant analysis (PLS-DA) analyses revealed clear differences in metabolites between HS and LS. Numerous metabolites and genes related to biosynthesis and downstream metabolic partitioning of shikimic acid were significantly differentially regulated. For instance, the transcript levels of malate dehydrogenase (MDH) and ribose-5-phosphate isomerase (RPI), that are involved in shikimic acid biosynthesis, were more upregulated in HS compared to LS. The abundances of tyrosine, tryptophan, luteolin and dihydromyricetin and the mRNA levels of chorismate synthase (CS), chalcone synthase (CHS), chalcone isomerase (CHI) and flavanone-3b-hydroxylase (F3H), that are implicated in downstream metabolism of shikimic acid were downregulated in HS compared to LS. Additionally, the abundances of abscisic acid and auxin in HS were lower than those in LS. Through association analysis, 27 metabolites, 33 structural genes and 28 transcription factors, such as ERFs, C2H2s and MYBs that play roles in shikimic acid accumulation were identified.ConclusionThese results suggest that metabolites and structural genes participating in biosynthesis and downstream metabolism of shikimic acids, and phytohormones and transcript factors play essential roles in shikimic acid accumulation in G. biloba leaves.